2012
DOI: 10.1186/1471-2164-13-582
|View full text |Cite
|
Sign up to set email alerts
|

First survey and functional annotation of prohormone and convertase genes in the pig

Abstract: BackgroundThe pig is a biomedical model to study human and livestock traits. Many of these traits are controlled by neuropeptides that result from the cleavage of prohormones by prohormone convertases. Only 45 prohormones have been confirmed in the pig. Sequence homology can be ineffective to annotate prohormone genes in sequenced species like the pig due to the multifactorial nature of the prohormone processing. The goal of this study is to undertake the first complete survey of prohormone and prohormone conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 84 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Our data showed the detection of most neuropeptide gene transcripts based on the reported information of approximately 100 genes identified in humans, rats, mice, pigs, cows and rhesus monkeys (Porter et al, 2012;Tegge et al, 2008). These derived expression profiles may guide future physiological studies focused on signal transduction and functions of these molecules in these two important tissues.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our data showed the detection of most neuropeptide gene transcripts based on the reported information of approximately 100 genes identified in humans, rats, mice, pigs, cows and rhesus monkeys (Porter et al, 2012;Tegge et al, 2008). These derived expression profiles may guide future physiological studies focused on signal transduction and functions of these molecules in these two important tissues.…”
Section: Discussionmentioning
confidence: 66%
“…Bioinformatic analysis (Porter et al, 2012) indicated a lack of a complete pig genome sequence for UCN1, UCN2 and UCN3 and was not supported by transcript evidence from UniGene, Gene, and UniProt. In our study, the expression of UCN1 and UCN2 was not observed, but UCN3 was expressed in Rongchang pig liver samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our systematic study of over 200 transcript isoforms produced by genes in the neuropeptide system enabled us to expose various MIA effects within gene and across brain regions that are subsequently exemplified. Transcript isoforms were identified in the hippocampus and hypothalamus for most neuropeptide and receptor genes known in mammals [16,17,38,39]. Transcript isoforms from neuropeptide Y receptor Y6 (NPY6R), insulin (INS) and urocortin 2 (UCN2) were identified in fewer than 5% of the pigs in both regions.…”
Section: Transcript Isoform Patterns Of Maternal Immune Activationmentioning
confidence: 99%
“…Neuropeptides are formed by enzymatic cleavage and chemical post-translational modifications of larger, inactive precursor proteins referred to as prohormones. In order to characterize these neuropeptides, the prohormone complement first needs to be revealed using sequence information and a list of known prohormones [28][29][30][31][32][33][34]. Ideally, the sequence information is obtained from the genome sequencing project of the species of interest but next-generation sequencing of the transcriptome can also be used for identification [35].…”
Section: Introductionmentioning
confidence: 99%